2020
DOI: 10.1002/adbi.202000062
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Proangiogenic Secretome from Mesenchymal Stromal Cells via Hierarchically Structured Biodegradable Microcarriers

Abstract: Adipose‐derived mesenchymal stromal cells (AdMSC) release numerous soluble factors capable of stimulating angiogenesis. Improved methods for delivering these cells to maximize their potency are now sought that ideally they retain viable cells in the target tissue while promoting the secretion of angiogenic factors. Substrate surface topography is a parameter that can be used to manipulate the behavior of AdMSC but challenges exist with translating this parameter into materials compatible with minimally invasiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 59 publications
2
13
0
Order By: Relevance
“…Higher magnification images of the microcarriers revealed many of the pores were distributed in a chevron pattern ( Figure 1C ). The size of the surface pores ranged from 0.17 to 2.40 μm, which corresponds with previous studies using the same composition of TIPS microparticles ( Simitzi et al, 2020 ). The porous structure of the microcarriers results from thermally induced separation that occurred during the manufacturing process ( Blaker et al, 2008 ).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Higher magnification images of the microcarriers revealed many of the pores were distributed in a chevron pattern ( Figure 1C ). The size of the surface pores ranged from 0.17 to 2.40 μm, which corresponds with previous studies using the same composition of TIPS microparticles ( Simitzi et al, 2020 ). The porous structure of the microcarriers results from thermally induced separation that occurred during the manufacturing process ( Blaker et al, 2008 ).…”
Section: Resultssupporting
confidence: 88%
“…The presence of ethanol in the wetting solution, a weak solvent for PLGA that does not dissolve the microcarriers during the wetting process, resulted in shrinkage of the hydrophilized microcarriers. Similar macroscopic shrinkage of PLGA scaffolds resulting from exposure to ethanol has been reported previously for TIPS microcarriers and other PLGA scaffolds ( Gualandi, 2011 ; Simitzi et al, 2020 ). Co-culture of the microcarriers with cAdMSC under optimized conditions resulted in efficient cell attachment within 18 h. The study screened two major parameters affecting cell attachment, namely the seeding concentration of cells and static-dynamic culture conditions.…”
Section: Discussionsupporting
confidence: 86%
“…For the hASCs, though, we did not observe differences in how the cells distributed themselves along the PLA disc compared to the 3D scaffolds, and there were no other differences in cell behavior in the analyzed parameters. However, some studies have shown the influence of scaffold topography on the paracrine activity of these cells ( Leuning et al, 2018 ; Simitzi et al, 2020 ). Su and colleagues (2017) showed that when hASCs were cultured on fibrous scaffolds, the cells produced more anti-inflammatory and pro-angiogenic cytokines than in a 2D culture.…”
Section: Discussionmentioning
confidence: 99%
“…Stem cell-based therapies aimed to improve functional results after prostatectomy need to promote regional postoperative angiogenesis both within the remaining of the sphincter and corpus cavernosa. The secretome of the MSCs includes proangiogenic factors extracellular vesicles (EV) carrying miRNAs (58). Regardless of the tissue of origin, enrichment of miRNAs in MSC-EVs has been shown to promote angiogenesis in vitro and in vivo.…”
Section: Vascular Regenerationmentioning
confidence: 99%